Validation of an opto-electronic instrument for the measurement of weighted countermovement jump execution velocity - Peña García-Orea, G.; Belando-Pedreño, N.; Merino-Barrero, J. A.; Jiménez-Ruiz, A.; Heredia-Elvar, J. R. (Sports Biomechanics, 2021)
The purpose of this study was to analyse the reliability and validity of an opto-electronic sensor system (Velowin) compared to a linear velocity transducer (T-Force System) considered as the gold standard. Mean velocity (MV) and peak velocity (PV) generated in the Smith machine bar placed on the shoulders in counter-movement jump exercise (CMJ) were analysed. The study was conducted with a sample of 21 men with experience in resistance training. Five measurements were analysed for CMJ exercise in concentric phase using a progressive loading increase. Three jumps were made per load with a 3?4min recovery between loads. The analysis of the variance confirmed that there were no significant differences (p>0.05) in the execution velocity between Velowin and T-Force with each of the loads. The reliability analysis showed, with each of the loads, high values of the intraclass correlation coefficient (ICC=0.95-0.99) and a -substantial- Lin's concordance coefficient in MV (CCC =0.96) and between -substantial-(CCC=0.98) and -lmost perfect- CCC=0.99) in PV. These results confirm the reliability and validity of the Velowin device is reliable for measuring the execution velocity in loaded CMJ exercise.